International Conference on Industrial Engineering and Systems Management (IESM '05 [ - Artiba, A.; Castagliola, Philippe (Journal of quality in maintenance engineering, 2008)
This e-book is devoted to the publication of six papers that were presented at the IESM'05 (International Conference on Industrial Engineering and Systems Management) held in Marrakech, Morocco, May 16-19, 2005. These papers cover different aspects of optimization, maintenance and quality.